Dyadic care to improve postnatal outcomes of birthing people and their infants: A scoping review protocol. - Courtney C Choy; Molly E McAdow; Julia Rosenberg; Alyssa A Grimshaw; Josefa L Martinez-Brockman (PLoS ONE)
Introduction Dyadic care, which is the concurrent provision of care for a birthing person and their infant, is an approach that may improve disparities in postnatal health outcomes, but no synthesis of existing dyadic care studies has been conducted. This scoping review seeks to identify and summarize: 1) dyadic care studies globally, in which the birthing person-infant dyad are cared for together, 2) postnatal health outcomes that have been evaluated following dyadic care interventions, and 3) research and practice gaps in the implementation, dissemination, and effectiveness of dyadic care to reduce healthcare disparities. Materials and methods Eligible studies will (1) include dyadic care instances for the birthing person and infant, and 2) report clinical outcomes for at least one member of the dyad or intervention outcomes. Studies will be excluded if they pertain to routine obstetric care, do not present original data, and/or are not available in English or Spanish. We will search CINAHL, Ovid (both Embase and Medline), Scopus, Cochrane Library, PubMed, Google Scholar, Global Health, Web of Science Core Collection, gray literature, and WHO regional databases. Screening will be conducted via Covidence and data will be extracted to capture the study design, dyad characteristics, clinical outcomes, and implementation outcomes. The risk of bias will be assessed using the Joanna Briggs Institute Critical Appraisal Tool. A narrative synthesis of the study findings will be presented. Discussion This scoping review will summarize birthing person-infant dyadic care interventions that have been studied and the evidence for their effectiveness. This aggregation of existing data can be used by healthcare systems working to improve healthcare delivery to their patients with the aim of reducing postnatal morbidity and mortality. Areas for future research will also be highlighted. Trail registration This review has been registered at Open Science Framework (OSF, https://osf.io/5fs6e/).